Small ruminants research and training needs assessment according to stakeholder’s perspective in Andalusia (South Spain) - Sayadi S.; Ruíz F.A.; Arrebola F.; Cruz J.L.; Parra López C.; Albisu L.M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The current situation of small ruminants’ sector in Spain is framed within a long process of restructuring associated with different national and international socio-political and economic challenges. In this framework, numerous studies confirm the importance of considering the opinions and perceptions of farmers to achieve all these challenges and highlight the weakness of agricultural research and training programs offered to meet farmers’ demands for specific knowledge. This must be facilitated by policy programs where agricultural research and training institutions play a key role. In order to fulfil that gap, the Institute of Agricultural Research and Training in Andalusia (IFAPA) organized several focus groups with different farming and livestock sectors to identify their priorities on research and training to be included in its Sector Program 2018-2021. In the case of small ruminants and framed with the National project RTA2015-00070-C03-02, we proposed to identify and quantify small ruminants’ sector real needs on research and training, to achieve greater productivity, competitiveness and sustainability. Thus, qualitative and quantitative methods were used during July 2018. Data were collected by a structured survey undertaken to 30 experts and a focus group organized with 25 livestock stakeholders (associations, cooperatives, research public institutes, universities, administration, etc.) related to the Andalusian livestock sectors. Results show that farmers have an integral view of their business by stating that they have to improve technological as well as commercial matters in order to be competitive.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)